Small boats, weak states, dirty money: piracy & maritime terrorism in the modern world - Murphy, Martin N. (Hurst, 2009)
What is piracy? -- Contemporary piracy : the who, the why and the where -- Contemporary piracy : irritation or menace? -- Maritime terrorism -- Maritime terrorists -- Assessing the threat